2016
DOI: 10.21273/hortsci11019-16
|View full text |Cite
|
Sign up to set email alerts
|

Handheld versus Mobile Data Acquisitions for Spatial Analysis of Natural Turfgrass Sports Fields

Abstract: Research compared handheld and mobile data acquisitions of soil moisture [volumetric water content (VWC)], soil compaction (penetration resistance), and turfgrass vigor [normalized difference vegetative index (NDVI)] of four natural turfgrass sports fields using two sampling grid sizes (4.8 × 4.8 m and 4.8 × 9.6 m). Differences between the two sampling grid sizes were minimal, indicating that sampling with handheld devices using a 4.8 × 9.6 m grid (120–130 samples) would achieve results similar to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Hand-held moisture meters have been employed to assess soil moisture and irrigation needs at a fine-scale resolution [9,10]. Time-domain reflectometry (TDR) has been used for smaller landscape areas to directly measure soil volumetric water content (VWC) [11][12][13][14]. Time-domain reflectometers are hand-held devices that consist of metal rods that emit high-frequency electromagnetic pulses through the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Hand-held moisture meters have been employed to assess soil moisture and irrigation needs at a fine-scale resolution [9,10]. Time-domain reflectometry (TDR) has been used for smaller landscape areas to directly measure soil volumetric water content (VWC) [11][12][13][14]. Time-domain reflectometers are hand-held devices that consist of metal rods that emit high-frequency electromagnetic pulses through the soil.…”
Section: Introductionmentioning
confidence: 99%
“…A missile of a known mass with an accelerometer on the end is dropped through a guide tube from a standard height (Clegg, 1976) Peak deceleration on impact at the surface reported as Gmax or gravities Number of missile drops at measurement locations vary in the literature and can influence values (Twomey, Ullah, & Petrass, 2014) Penetrometer Penetration resistance A cylindrical cone at the end of a shaft penetrates the surface to a certain depth by dropping a weight from a standard height down the shaft or pushing down on the shaft manually (Orchard, 2001;Straw et al, 2016) Depth of soil penetration (e.g., cm) or force required to penetrate a soil to a certain depth (e.g., MPa; measured by a load cell)…”
Section: Clegg Impact Testermentioning
confidence: 99%
“…User can influence sampling technique that involves pushing down on the shaft manually (Straw et al, 2016;Twomey et al, 2011) Spectral reflectance sensors…”
Section: Clegg Impact Testermentioning
confidence: 99%
“…Previous performance testing studies (with and without spatial methods) have concluded that considerable variations within field properties exist on natural turfgrass sports fields (Bell & Holmes, 1988;Caple et al, 2012aCaple et al, , 2012bStraw, Grubbs, Tucker, & Henry, 2016). This may be attributed to environmental conditions, turfgrass species, soil texture, management practices, and the amount and location of field usage.…”
Section: Introductionmentioning
confidence: 99%